Patients’ willingness to provide their clinical data for research purposes and acceptance of different consent models: findings from a representative survey of patients with cancer - Köngeter, Anja; Schickhardt, Christoph; Jungkunz, Martin; Bergbold, Susanne; Mehlis, Katja; Winkler, Eva C. (Journal of medical internet research)
Background: Secondary use of clinical data for biomedical research purposes holds great potential for various types of noninterventional, data-driven studies. Patients’ willingness to support research with their clinical data is a crucial prerequisite for research progress. - Objective: The aim of the study was to learn about patients’ attitudes and expectations regarding secondary use of their clinical data. In a next step, our results can inform the development of an appropriate governance framework for secondary use of clinical data for research purposes.